Exploring e-psychonauts perspectives towards cocaine effects and toxicity - Sulaf Assi; Aidan Keenan; Abdullah Al Hamid (BMC, 2022)
Abstract Background According to the World Drug Report, cocaine is the second most used drug globally after cannabis. Online discussion forums enable the understanding of authentic drug users' experience as it is anonymous. Therefore, this study determined the uses, effects and toxicity of cocaine from the perspectives' of e-psychonauts. Methods A qualitative study was conducted using six popular discussion forums. From these discussion forums, 1229 posts from 50 threads were subject to thematic analysis. Hence, the information from these threads were examined carefully for patterns and codes among the data. The codes were then collated into subthemes and themes. Results The four main themes emerging from the study were related to cocaine characteristics and use, e-psychonauts' knowledge and experience, desired effects and adverse events. The main characteristic associated with cocaine use was purity that was highest in the US being nearest to the source. The most common cutting agent encountered in cocaine samples was levamisole that increased the chances of immunosuppression and cardiovascular toxicity. Purity depended on the source of purchase that included street dealers, dark web and surface web. Hence, e-psychonauts recommended purchase of cocaine from known dealers rather than websites with unknown sources. E-psychonauts mainly used cocaine in social context and parties or to self-medicate against anxiety and depression. Effects desired from cocaine use were mainly euphoria and increased energy. However, tachycardia and myocardial infarction were the main adverse events. It is noteworthy to mention that myocardial infarction was idiosyncratic and was often lethal. Myocardial infarction was more often reported when cocaine was combined with alcohol due to the production of cocaethylene. Social harm was also reported as a consequence for the use of cocaine that resulted in homelessness and broken relationships. Conclusion Online discussion forums allowed the understanding of e-psychonauts' experience with cocaine use. Not only it informed about the sources and modalities of use of cocaine but also about the adverse events and social harm associated with cocaine use. The present findings serve as useful information for practitioners and healthcare professionals dealing with cocaine users.